Optimization of the physical fitness control system for cadets of higher military educational institutions - Petruk , Andrii; Romanchuk , Serhii; Viacheslav, Viacheslav; Anokhin , Yevhen; Danylevych , Myroslava; Kurbakova , Svitlana (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. A mandatory element of the training system in Higher Military Educational Institutions (HMEIs) is the assessment and evaluation of cadets’ physical fitness. This is carried out in accordance with the provisions of the Physical Training Instruction within the Ministry of Defense of Ukraine. Since the establishment of independent Ukraine, the governing documents on physical training have been refined in 1997, 2009, 2014, and 2021. The system for assessing the physical fitness of military personnel (cadets) has remained unchanged over all these years. It involves testing according to a specific list of exercises and evaluating performance based on developed standards. The functional state of the performers’ bodies and their moral-psychological (motivational) condition were not taken into account. In our opinion, this is a significant shortcoming of the existing system for assessing and evaluating the physical fitness of military personnel, especially cadets in HMEIs. The aim of the study is to develop an author’s program to monitor first-year cadets’ mastery of the discipline of “Physical Education and Special Physical Training” in higher military educational institutions (HMEIs). Materials and Methods of the Study. The research was conducted at the Hetman Petro Sahaidachnyi National Army Academy. During the study, an analysis was performed on the educational programs of various higher military educational institutions, as well as the authors’ physical training programs for cadets of different military specialties and branches of the military. To achieve the set objectives, methods of theoretical analysis and synthesis of literary sources, documentary materials, and practical implementation of control measures during cadets’ training were utilized. Results. The study revealed that the assessment and evaluation of the physical fitness of military personnel (cadets in HMEIs) is a mandatory element of the training system in all structures of the Armed Forces of Ukraine, including HMEIs. However, the assessment only covers the level of development of physical qualities and the degree of mastery of certain military-applied skills. We have developed and proposed certain adjustments to the system of physical fitness control for HMEI cadets. Specifically, control should be conducted in four areas: assessment of the level of physical fitness (based on a set of certain physical exercises); assessment of the functioning state of the cardiovascular system; assessment of the moral and psychological state (level of motivation for physical training); and assessment of the level of theoretical knowledge regarding the impact of physical exercises on human health. Conclusions. Based on the analysis of the existing system for assessing physical fitness in HMEIs and the research materials on the educational activities of cadets, a new system for assessing and evaluating the physical fitness of HMEI cadets has been developed and proposed.